2019
DOI: 10.3390/molecules24081462
|View full text |Cite
|
Sign up to set email alerts
|

Postharvest UV-B Irradiation Stimulated Ginsenoside Rg1 Biosynthesis through Nitric Oxide (NO) and Jasmonic Acid (JA) in Panax quinquefolius Roots

Abstract: The study highlights the influence and signal transduction mechanism of postharvest UV-B on the production of Rg1 in Panax quinquefolius roots during the drying process. The results showed that postharvest UV-B irradiation induced generation of nitric oxide (NO), jasmonic acid (JA), and ginsenoside Rg1 of P. quinquefolius roots. The UV-B-induced increase of Rg1 was suppressed by NO-specific scavenger (cPTIO) and NOS inhibitors (PBITU), JA synthesis inhibitor (SHAM), and JA synthesis inhibitor (PrGall), indicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…In most studies where UV-B radiation has been manipulated, it has been applied prior to harvest (i.e., preharvest), or following harvest (i.e., postharvest). Species studied in this context include beetroot [ 200 ], broccoli [ 201 ], ginseng [ 202 ], prickly pear [ 203 ], blueberry [ 204 ], and even mushrooms [ 205 ]. In certain varieties of peach, these treatments have helped maintain the weight, firmness, and vitamin C content of the fruit, which increases its quality, value, and shelf-life [ 206 208 ].…”
Section: Terrestrial Ecosystems and Biodiversitymentioning
confidence: 99%
“…In most studies where UV-B radiation has been manipulated, it has been applied prior to harvest (i.e., preharvest), or following harvest (i.e., postharvest). Species studied in this context include beetroot [ 200 ], broccoli [ 201 ], ginseng [ 202 ], prickly pear [ 203 ], blueberry [ 204 ], and even mushrooms [ 205 ]. In certain varieties of peach, these treatments have helped maintain the weight, firmness, and vitamin C content of the fruit, which increases its quality, value, and shelf-life [ 206 208 ].…”
Section: Terrestrial Ecosystems and Biodiversitymentioning
confidence: 99%
“…Although research on NO‐mediated protein nitration in regulating the activity or functions of target proteins is mostly conducted in animals and plants, researchers have also gradually discovered that NO can regulate SM synthesis in plants and fungi. In Panax quinquefolius , NO plays essential role in UV‐B‐induced Rg 1 production (Zhou et al ., 2019). NO could induce the artemisinin biosynthesis by stimulating gene expression and enzyme activity involved in artemisinin biosynthesis in Artemisia annua (Wang et al ., 2009).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to these nitrogen regulatory genes, nitric oxide (NO) produced during nitrogen metabolism has also been reported to influence SM biosynthesis in many species (Baidya et al ., 2011; Zhou et al ., 2019; Zhu et al ., 2019). It is a cellular signalling molecule that functions from yeast to mammals.…”
Section: Introductionmentioning
confidence: 99%
“…In another study carried out on S. miltiorrhiza hairy roots, it was shown that the phytohormones, gibberellin, ethylene, and abscisic acid all effectively enhanced the activities of tyrosine aminotransferase (TAT) and phenylalanine ammonia lyase (PAL), and induced the production of caffeic acid, rosmarinic acid, and salvianolic acid [116]. The ginsenosides (glycosylated triterpene) yield in the hairy root culture of Panax quinquefolium, when elicited with MeJA for 7 days, reached maximum to 51.0 mg g À1 DW in bioreactor and 27.33 mg g À1 DW in shake flask [117]. In Vitis vinifera subsp.…”
Section: Chemical Elicitorsmentioning
confidence: 99%